2008
DOI: 10.1007/s00403-008-0832-7
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of PKD1 in normal human epidermal keratinocytes increases mRNA expression of keratin 10 and involucrin: early markers of keratinocyte differentiation

Abstract: Subconfluent normal human keratinocytes exhibit autonomous (autocrine growth factor driven) proliferation and express the specific markers for keratinocyte proliferation K5 (keratin 5) and K14 (keratin 14). Utilizing this model the effects of PKD1 (Protein kinase D1) knockdown on activation of differentiation was studied. siRNA approach was applied to achieve specific knockdown of PKD1 and the mRNA levels of different keratinocyte markers -- K14 and PCNA (markers of basal proliferating keratinocytes), involucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…This increase was observed in PKD1-deficient keratinocytes under basal as well as differentiating conditions. Similar to our results, siRNA-mediated PKD1 knockdown in human keratinocytes resulted in increased involucrin mRNA expression [24]. Also, we have previously reported that PKD overexpression with an involucrin promoter reporter constructs results in decreased promoter activity [21].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This increase was observed in PKD1-deficient keratinocytes under basal as well as differentiating conditions. Similar to our results, siRNA-mediated PKD1 knockdown in human keratinocytes resulted in increased involucrin mRNA expression [24]. Also, we have previously reported that PKD overexpression with an involucrin promoter reporter constructs results in decreased promoter activity [21].…”
Section: Discussionsupporting
confidence: 90%
“…These results confirm that PKD1 is an anti-differentiative and pro-proliferative signaling enzyme in mouse keratinocytes, similar to human keratinocytes [24], but are unique in that they were obtained with the use of the floxed PKD1 mouse model rather than overexpression [40] or RNA interference [24], with the attendant caveats of these methods. Thus, in this study, we used PKD1-floxed mice that possess loxP sites flanking exons 12 through 14 of the PKD1 gene, which encodes part of the catalytic domain.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…KCs-Previous studies have indicated that PKD1 is expressed in human skin and is up-regulated in hyperproliferative skin disorders (4,20). To further investigate the role of PKD1 in human epidermis, we used lentivirus-mediated shRNA to knockdown PKD1 in NHKCs.…”
Section: Divergence In Pkd Expression and Function Between Mouse And mentioning
confidence: 99%